Monetary Reward Effects in Discrimination and Neurophysiological Activity During Use of a Tactile Stimulation Sleeve - Pais-Vieira, Carla (2022)
The development of devices capable of delivering tactile and thermal feed-back have the potential to improve brain-machine interfaces for neuroreha-bilitation protocols. Monetary rewards are known to improve some types of passive tactile processing. The aim of this study was to describe the perfor-mance and neural activity of subjects receiving tactile stimuli through a tac-tile stimulation sleeve in the presence or absence of monetary rewards. Healthy subjects were required to discriminate between different tactile stim-ulation patterns delivered through a stimulation sleeve while their neural ac-tivity was recorded with Electroencephalography (EEG). Behaviorally, no significant differences were observed in the performances of subjects wear-ing the sleeve. Meanwhile, analysis of neural activity revealed that the intro-duction of monetary rewards consistently generated significant differences in theta frequency band for occipital electrodes. These results support the no-tion that monetary rewards can significantly influence tactile information processing.